SHIFTING FROM TEACHER-CENTERED TO LEARNER-CENTERED INSTRUCTION IN LANGUAGE CLASSROOMS - Arazmuratova Hulkar Omirbek qizi; Karabayeva Munisa To’lqin qizi; Anorboyeva Saodat (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper explores the transition from teacher-centered to learner-centered instruction in language classrooms, emphasizing its benefits, implementation strategies, and challenges. It highlights how active learning enhances student engagement, autonomy, and communicative competence.